Food Handling & Food Savety Training bagi Pengelola Kuliner - Permana, Dimas Ero; Pearl Loesye Wenas; Merryany Bawole; Margresya Rompas; Frans Victor Rattu (Jurnal Ragam Pengabdian, 2025)
Consumers have become increasingly concerned about food quality and safety in the last decade. Fostering and maintaining guest confidence in food quality and safety requires the role of quality assurance departments in the food sector.  These guidelines consist of the basic principles, procedures, personal hygiene and means necessary to design and maintain an environment suitable for producing acceptable quality food.  Budo Tourism Village has 15 culinary operators and 11 tourist facilities and so far there have been no cases of culinary mismanagement causing illness or casualties to visitors.  However, during observations of tourist sites, and facilities owned by culinary arrangements are still classified as below standard and the cleanliness of waiters and culinary managers has not been maximized. Discussion and practice methods were used in this training. The results show that the level of understanding of the participants is quite responsive, this is indicated by six assessment indictors, namely: cleanliness and sanitation, separation of food ingredients, cooking properly, storage of food ingredients, selection of raw materials and dining table set-up. Furthermore, the assessment of the presenters by the participants related to the content of the material and delivery, on average participants answered with interesting and mastering.